The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s13679-016-0192-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perceived Healthiness of Food on Food Choices and Intake

Abstract: Healthy eating is an important determinant of health, but adherence to dietary guidelines remains a public health concern. Identifying factors that impact dietary habits are therefore important to facilitate healthy eating. One widely used strategy to help consumers make healthier food choices is nutrition information, such as labeling and claims. Despite the intention of these strategies to improve decision making, they can also be misunderstood or misinterpreted by consumers. The aim of this review is to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 43 publications
1
57
0
2
Order By: Relevance
“…The labelling manipulation thus likely had reduced impact on the cookies because they are not a diet-congruent food item. It is also in accordance with the conclusion of recent review from Provencher and Jacob [46] which states that labelling influences health perception but that the impact on energy intake is less consistent.…”
Section: Discussionsupporting
confidence: 92%
“…The labelling manipulation thus likely had reduced impact on the cookies because they are not a diet-congruent food item. It is also in accordance with the conclusion of recent review from Provencher and Jacob [46] which states that labelling influences health perception but that the impact on energy intake is less consistent.…”
Section: Discussionsupporting
confidence: 92%
“…The 'health halo' effect is a type of cognitive bias whereby an inference of health is assumed based on ambiguous information or claims, which may also explain the findings of this review [80]. Several systematic reviews [77,81,82] have identified an organic 'health halo' with consumers viewing organic as a healthier alternative to conventional products, despite a lack of convincing evidence that organic foods are nutritionally superior [83,84].…”
Section: This Review's Findings In Contextmentioning
confidence: 89%
“…Consumption of health-related products reflects people's concerns about the living environment, their own health, and animal welfare [42]. Eating healthy food is also an important factor in determining human health [43]. As such, researchers highlighted that perceived healthiness affects consumer evaluation and choice of products [41], which are all important indicators of market development and promotion of healthy eating [44].…”
Section: Visitors' Motivesmentioning
confidence: 99%